A Novel Sediment Pressure Sampling Device Carried by a Hadal-Rated Lander - Jiawang Chen; Yue Huang; Yuan Lin; Peng Zhou; Yuping Fang; Xiaoling Le; Yuhong Wang (Journal of Marine Science and Engineering, 2020)
Reliable sampling technology for deep-sea sediments is a prerequisite for studying the sedimentary environment in the geological history, the mechanical characteristics of sediments and sediment biology. In this study, we develop a new sampling device in order to achieve a convenient and economic pressure sampling for hadal sediments. The overall structure, as well as the key component such as the pressure-holding part, and the sealing structure are designed. The feasibility of the device was verified through field tests. Furthermore, the sampling process is analyzed by the computer simulation. It is found that the sampling length is determined by the open diameter and the installation position of the core keepers. According to the simulation, the structure is optimized, which is beneficial to the further improvement of the sampling length.